ZESA I.T support ticket management system - Zongoro, Keith (Midlands State University, 2018)
The purpose of this research was to come up with a solution to problems that were being faced at the ZESA I.T department with regards to the way users report issues to the helpdesk and how support officers respond to these issues. ZESA I.T Support Ticket Management System is a web-based automated computer system that sets smart rules to prioritize and automatically assign support tickets to support officers and administrators. The end users or customers submit tickets regarding their issues to the intended helpdesk department which is automatically assigned to a helpdesk agent who then works on the issue until it is resolved and replies the resolved issue to the end user. Its major thrust is to provide a simple and easy platform to serve end users faster with help desk automation that automates repetitive tasks using smart help desk workflows. The system will eliminate the current problems that are being faced by the current system were users get responses from the I.T department late regarding their issues. ZESA uses quite a number of applications that need to be supported when users face difficulties and they are different support officers who specialize in those applications. The system was developed to address the weaknesses of the old system. MYSQL, MAMP, Sublime Text Editor php, css, java scripts and Microsoft word 2011 are the instruments that were used in the development of the new system.